Synthesis and luminescence properties of Sr3MgSi2O8:Ce3+, Tb3+ for application in near ultraviolet excitable white light-emitting-diodes. (December 2016) - Chen, Yan; Zhou, Bin; Sun, Qimeng; Wang, Yongqian; Yan, Bing
Abstract: The alkaline-earth silicate Sr3 MgSi2 O8 :Ce 3+, Tb 3+ phosphors have been synthesized via conventional high temperature solid-state method. The crystal structure, luminescence properties, morphology of phosphors are investigated systematically. The thermal quenching and concentration quenching mechanisms of phosphors are also discussed. The phosphors can be excited under near ultraviolet light ranging from 200 nm to 450 nm. The calcination temperature and calcination time are significant factors for luminescence property of phosphors. Increasing co-doping Tb 3+ makes the emission intensity of Ce 3+ decreases proportionally while the emission of Tb 3+ increases. It indicates that it exists energy transfer between Ce 3+ and Tb 3+ . The emission wavelength can be tuned from bluish violet region to blue region. The results imply Sr3 MgSi2 O8 :Ce 3+, Tb 3+ phosphors can be a potential candidate for solid-state lighting. Highlights: A series of wavelength-tunable Sr3 MgSi2 O8 :Ce 3+, Tb 3+ phosphors were obtained. The luminescence properties were enhanced by doping Ce 3+ . The concentration quenching and thermal quenching of phosphors were primary factors for degrading luminescence performance. Sr3 MgSi2 O8 :Ce 3+, Tb 3+ phosphors can be a potential candidate for application in UV white-light-emitting diodes.